2009
DOI: 10.1016/j.jcin.2009.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Total Occlusion Angioplasty in the United States

Abstract: Coronary chronic total occlusions (CTOs) are commonly encountered complex lesions identified in 15% of all patients referred for coronary angiography. Chronic total occlusion remains the most powerful predictor of referral for coronary bypass surgery. The benefits of CTO percutaneous coronary intervention (PCI) include symptom relief, improved left ventricular function, and potentially a survival advantage associated with success when compared with failed CTO-PCI. Data from the NCDR (National Cardiovascular Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
182
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(191 citation statements)
references
References 42 publications
3
182
1
5
Order By: Relevance
“…Several studies showed that CTO patients are a high-risk population with more traditional cardiovascular risk factors, multivessel disease, history of MI and PCI (Fefer et al, 2012;Grantham et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that CTO patients are a high-risk population with more traditional cardiovascular risk factors, multivessel disease, history of MI and PCI (Fefer et al, 2012;Grantham et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Chronic total occlusions (CTOs) of coronary arteries are complex lesions present in approximately 30% of patients undergoing coronary angiography (Grantham et al 2009). CTOs are defined, as lesions present for at least 3 months with grade 0 to 1 Thrombolysis in Myocardial Infraction (TIMI) flow on angiography.…”
Section: Defining Coronary Anatomy Prior To Cto-pcimentioning
confidence: 99%
“…The true incidence of CTO in the general population is not known due to a large proportion of asymptomatic or oligosymptomatic cases. In angiographic studies CTO is found in 20-40% of patients with established coronary artery disease [1][2][3][4]. For many years, CTO was a major indication for surgical myocardial revascularisation or continued medical therapy.…”
Section: Introductionmentioning
confidence: 99%